Information Literacy of Post-Graduate Students and Research Scholars: A Study of Mizoram University - Lallaisangzuali (Journal of Information and Knowledge, 2015)
Information Literacy is conceivably the foundation for learning in our contemporary environment of continuous technological change. As Information and Communication Technologies (ICTs) develop rapidly, and the information environment becomes increasingly complex, developing Information Literacy among students and Research Scholars for lifelong learning is a vital element. The paper aims to explore the status of Information Literacy of Post-Graduate Students and Research Scholars of Mizoram University, Aizawl, their information seeking skills and ability to acquire and use information effectively. A structured questionnaire was distributed among the students and Research Scholars to collect the necessary primary data. The results of the investigation provide useful information about the Information Literacy of the Post-Graduate Students and Research Scholars.